Impact of UASB reactors operation mode on the removal of estrone and 17α-ethinylestradiol from wastewaters - Louros, Vitória L. (2023)
This work aims to compare the performance of the continuous operation (CO) and intermittent operation (IO) of upflow anaerobic sludge blanket (UASB) reactors for the removal of estrone (E1) and 17α-ethinylestradiol (EE2) from wastewaters. Results suggest that the IO contribute to the improvement of the overall removal of estrogens (above 95% for E1 and EE2) when compared to CO (49% for E1 and 39% for EE2). For both CO and IO, biodegradation was the main removal mechanism for E1, while for EE2, adsorption to sludge was the major removal pathway. Moreover, a higher biodegradation of estrogens was obtained with the IO compared to CO (69.4% vs. 43.3% for E1 and 21.8% vs. 8.0% for EE2). The favourable effect of IO can be justified by effluent recirculation during the feedless period which promotes the adaptation of microbial biomass to estrogens' biodegradation.